On Action, Embeddedness, and Institutional Change - Cardinale, Ivano (Academy of Management Review, 2019)
The article starts by discussing competing interpretations of actors’ embeddedness in structure. To do so, it distinguishes between constraints on action imposed by structure at the individual and social level, and renders action as resulting from how actors engage with such forms of structure through different types of agency. The article goes on to argue that a diachronic understanding of the mutual constitution of actions and structure, whereby they are relatively autonomous at a given moment while shaping each other over time, is the most fruitful for studying institutional change.